Rapid and specific diagnosis of t(11;22) translocation in paediatric Ewing's sarcoma and primitive neuroectodermal tumours using RNA-PCR. Issue 6 (June 1994) - Diffin, F; Porter, H; Mott, M G; Berry, P J; Brown, K W
Abstract : One case of paediatric Ewing's sarcoma and two peripheral primitive neuroectodermal tumours/extra-osseous Ewing's sarcoma were studied for the characteristic t(11;22) translocation, using a recently described RNA-polymerase chain reaction method (RNA-PCR). PCR products of the expected sizes were obtained from RNA derived from the Ewing's sarcoma and the peripheral primitive neuroectodermal tumours, but not from other paediatric malignancies. Direct sequencing of the RNA-PCR products confirmed the presence of the EWS-FLI-1 fusion transcript. In one case the presence of the translocation was confirmed by cytogenetic analysis. These results highlight the potential use of PCR for the rapid demonstration of diagnostically important tumour specific chromosome rearrangements.